Cooperative Debate Can Provoke Multiperspectivity - Jacobs, George M; Wu, Yingrui; Wen, Yi (Autonomy and Responsibility Journal of Educational Sciences, 2024)
The purpose of this article is to recommend the Cooperative Debate technique as a means of encouraging students and others to view the world via a multitude of perspectives. Cooperative debates are contrasted with traditional competitive debates, with cooperative debates recommended for their greater focus on growing understanding, rather than on winning a debate contest. A flexible, eight-step procedure for the Cooperative Debate technique in the cooperative learning approach is described. In this procedure, each person presents two or three different perspectives on the topic being discussed. Cooperative Debate can also include consideration of how debaters and their audience might seek to implement their views. Social Interdependence Theory and Piagetian Theory are used to provide insights into the workings of Cooperative Debate.